Beyond bones and teeth: Langer–Giedion syndrome revealed through oral and psychiatric clues — a multisystem case report - P., Shibhu; Jacob, Anieta Merin; B. S., Chandrashekar; Joseph, Alvin; Suresh, Kevin Emmanuel; Abraham, John (International Journal of Research in Medical Sciences, 2026)
Langer–Giedion syndrome (LGS), also known as trichorhinophalangeal syndrome type II (TRPS II), is a rare contiguous gene deletion disorder involving chromosome 8q24.11–q24.13, resulting in loss of the TRPS1 and EXT1 genes. The syndrome is characterized by distinctive craniofacial dysmorphism, multiple osteochondromas, skeletal abnormalities, intellectual disability, and dental anomalies. Psychiatric and neurodevelopmental manifestations remain underreported despite their significant impact on functioning and quality of life. We report a 19-year-old female who presented with dental pain and was subsequently found to have classical craniofacial, skeletal, oral, neurodevelopmental, and psychiatric features consistent with Langer–Giedion syndrome. Clinical examination revealed microcephaly, a bulbous nasal tip, prominent ears, multiple bony exostoses, short stature, hypodontia, malocclusion, and retained deciduous teeth. Developmental history demonstrated delayed motor milestones, while psychiatric evaluation revealed borderline intellectual functioning, social immaturity, and emotional dysregulation. Radiographic imaging demonstrated multiple enchondromas and impacted teeth. This case emphasizes the importance of recognizing oral and behavioural manifestations as diagnostic clues in rare genetic syndromes and underscores the necessity of multidisciplinary management incorporating psychiatric care.